Foreign Literature in Fascist Italy: Circulation and Censorship - Dunnett, Jane (TTR, 2002)
AbstractIn this article the author sets out to illustrate some of the strategies which Italian translators and publishers adopted, or were forced to adopt, to ensure that their texts passed muster under Fascism. “Taboo” areas are identified and an attempt is made to sketch out what were often rather vague criteria for acceptability. The author proceeds to survey the mechanisms that were put in place to vet books—essentially, preventive censorship and police confiscation—for the duration of the dictatorship. It is argued that the apparatus of the State was only partially successful at monitoring the content of works of literature. This historical contextualisation, drawing on archival and published material, is followed by a number of case-studies, first of three novels by John Steinbeck, and then of Americana, a famous anthology of American literature published during the Second World War. In her conclusion, the author draws attention to the failure of the regime to implement a watertight policy on translation, despite its desire to influence the way readers interpreted books.